The balance of nitrogen, calcium and phosphorus in lactating cows - Tyurina, L E (Mongolian Journal of Agricultural Sciences, 2018)
More relevant for today give to the use of unconventional sources of minerals, one such source can serve as a waste alumina production - believei sludge.